Pengaruh Sri Sultan Hamengku Buwono I pada Seni Karawitan Kraton Yogyakarta - -, Raharja; Haryono, Timbul; Soedarsono, R.M.; Susanto, Adhi (Resital: Jurnal Seni Pertunjukan, 2014)
Gamelan sebagai alat musik atau karawitan sebagai produk musikal dari Kraton Yogyakartamempunyai beberapa karakter yang sangat khas. Karawitan masih dipergunakan sebagai suatu identitasdan diakui oleh masyarakat hingga saat ini. Pengembangan musikal ini bermula dari Sri SultanHamengku Buwono I. Ada dua alasan penting yang mendorong gagasan penciptaan karaktergamelan. Pertama, konsepsi kedudukan raja telah mendudukkan gamelan sebagai salah satu pusakapenting. Kedua, kepribadian Sultan yang maskulin, heroik, dan patriotik menjadi model pengembangan,memberi ciri khas pada masing-masing ricikan gamelan dan musikalitasnya. Gamelan KratonYogyakarta mempunyai kesan rasa musikal: agung, gagah, tegas, mantap, berwibawa, mrabu (sepertiraja), dan ngratoni (seperti suasana di kraton). The Effect of Sri Sultan Hamengku Buwono I on Kraton Yogyakarta Karawitan. Gamelan asmusical instrument or karawitan as a musical product of Kraton Yogyakarta has some specific characters. Itis still used as an identity and is recognized by karawitan society until now. This musical development wasfirstly introduced by Sri Sultan Hamengku Buwono I. There are two important reasons which stimulatethe ideas of creating gamelan characters. First, the king’s authority conception puts the gamelan as one ofthe important heirloom. Second, Sultan’s personalities which are masculine, heroic, and patriotic becomethe influencing model of its development, and give some specific characters on each gamelan instrument andits musicality as well. Kraton Yogyakarta gamelan has many musical rasa(s)/feelings: glorious, strong, clear,steady, prestigious, ‘mrabu’ (like a king), and ‘ngratoni’ (such an atmosphere of Kraton).